The Effect of Flag Ceremony Implementation on The Nationalism Attitude of Student of Putera Harapan Three Language Elementary School - Sasmita, Cahyudi Dwi; Aryani, Ine Kusuma (Universitas Muhammadiyah Surakarta, 2024)
These This study to determine how the implementation of the flag ceremony affects the nationalism attitude of students at the Putera Harapan Purwokerto Three Language Elementary School, which is predominantly of ethnic Chinese descent. Data collection and processing using quantitative research methods with questionnaires. The questionnaire is a measuring tool used to measure student attitudes with a Likert scale, with answer items: a) STS = Strongly Disagree, b) TS = Disagree, c) N = Neutral, d) S = Agree, el) SS = Strongly Agree, in using a research scale the conversion guidelines for PAN can use a scale of four, five, nine and so on (Nurgiyantoro, 2012). The results of this study indicate that there is an effect of the implementation of the flag ceremony on students' nationalism attitudes which shows that 10 students (33.3%) are in the very good category, 10 students (33.3%) are in the good category, 8 students (26.7%) are in the poor category and 2 students (6.7%) are in the very poor category. This data shows that the distribution of student attitude scores about the flag ceremony is obtained above the average, so it can be said that the majority of students' national attitudes towards flag ceremony activities are in the good category.